The existence of adrenal insufficiency in patients with COVID-19 pneumonia - Porntharukchareon, Thachanun; Dechates, Bothamai; Sirisreetreerux, Supamas; Therawit, Phonthip; Tawinprai, Kriangkrai (Frontiers in Endocrinology, 2024)
Introduction Infection with SARS-CoV-2 virus may result in long COVID, a syndrome characterized by symptoms such as dyspnea, cardiac abnormalities, cognitive impairment, and fatigue. One potential explanation for these symptoms is hypocortisolism. Objective To evaluate the prevalence of hypocortisolism in patients with a history of COVID-19 pneumonia. Methods Cross-sectional study of patients who were aged ≥18 years and had a 3-month history of radiography-confirmed COVID-19 pneumonia. Exclusion criteria included current or previous treatment with glucocorticoids and use of an oral contraceptive. Adrenal function was evaluated using a low dose (1ug) corticotropin stimulation test (CST). Serum cortisol levels were measured at 0, 30, and 60 minutes, and baseline plasma ACTH was also measured. Results Of the 41 patients enrolled, the median age was 62 years, 17 (42%) were female, and all 41 (100%) had severe pneumonia at baseline. Eleven patients (27%) had hypocortisolism, as evidenced by peak cortisol of less than 402.81 nmol/l after low dose (1 µg) CST. Of these 11 patients, 10 (91%) had secondary hypocortisolism (median ACTH 6.27 pmol/L, range 4.98–9.95 pmol/L) and one had primary hypocortisolism (mean ACTH 32.78 pmol/L). Six of the 11 patients with hypocortisolism (54.5%) reported symptoms of persistent fatigue and 5 (45.5%) required regular glucocorticoid replacement. Conclusions Our results suggest that hypocortisolism, predominantly caused by pituitary disruption, may emerge after SARS-CoV-2 infection and should be considered in patients with a history of COVID-19 pneumonia with or without clinical hypocortisolism.